Activity of bismuth in liquid Ag-Bi-Ni alloys determined by equilibrium saturation method - Fima P.; Romanowska J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Activity coefficients of Bi in liquid Ag-Bi-Ni alloys were experimentally determined by means of the equilibrium saturation method at 1173 and 1273 K. The measurements were carried out for alloy compositions along three sections of fixed Ag to Ni mole fraction ratio equal to 4/1, 3/2, and 2/3. The excess Gibbs free energy of Bi was calculated basing on the experimental activity coefficient data. The experimental activity data were compared to the values calculated for two sets of assessed thermodynamic data.